Key Stakeholders And Mandatory Disclosure in Local Government Financial Statements in Java - Tadjuddin Tadjuddin; Jumarni Jumarni; Andi Nurrahma Gaffar; Muhammad Ikram; Uswatun Hasanah; Muh. Fiqran (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study examines the influence of key stakeholders, such as the educational background of regional heads, the number of legislative members, the education of legislative members, the number of local government employees, and Regional Original Revenue (PAD) on compliance with mandatory disclosure in local government financial statements. Hypothesis testing was carried out using SPSS release 17 software. The population in this study is all regional heads (regional heads), PEMDA employees, members of the DPRD, PAD, DAU and local government financial statements in Java. The results of statistical analysis show that the level of compliance with mandatory disclosure in Java is still very low, with an average of only 25.27%, indicating that many local governments have not fully complied with the Government Accounting Standards (SAP). Ciamis Regency recorded the highest compliance with 41.18%, while Pati Regency was the lowest with only 8.82%.